Impact of micronutrients and organics on performance of sprouting broccoli (Brassica oleracea) - NETWAL, MANJU; SINGH, S P; GARHWAL, O P; JAKHAR, RAJ KUMAR; CHOYAL, PRAVEEN; CHOUDHARY, GULAB; NEHRA, ANJU (The Indian Journal of Agricultural Sciences, 2023)
An experiment was conducted during winter (rabi) seasons of 2019–20 and 2020–21 at the research farm of Sri Karan Narendra Agriculture University College, of Agriculture, Jobner, Rajasthan to study the effect of micronutrients and organics on performance of sprouting broccoli (Brassica oleracea L.). A trial having 25 treatments was conducted in Factorial Randomized Blocks Design (F-RBD) with 3 replications. The treatments grouped into categories consisting 5 micronutrients (control, borax @15 kg/ha, Znso4 @25 kg/ha, (NH4)2MoO @1.5 kg/ha and Mnso4 @10 kg/ha) and another category consisted 5 organics (control, cowurine @10%, panchagavya @5%, vermiwash @10% and azotobacter). The results indicated that soil application of Znso4 as well as foliar application of 5% panchagavya to the sprouting broccoli significantly increased most of the plant attributes i.e. plant hight (71.88 cm and 71.95 cm), no. of leaves/plant (31.38 and 31.12), leaf area (3055 cm2 and 3068 cm2), chl-a (2.90 mg/g and 3.09 mg/g), total curd yield per ha (28.81 Mt/ha and 29.41 Mt/ha), NR (224848 `/ha and 230256 `/ha) and BCR (3.55 and 3.60), respectively in comparison to the control. Application of ZnSO4 and panchagavya contributed 24.72 and 26.49%, respectively more in total curd yield per hectare as compared to control. Thus, findings of experiment were in conclusion that application of ZnSO4 @25 kg/ha in soil and application of panchagavya @5% as foliar spray have the prospective effect to enhance all attributes in sprouting broccoli not only in comparison to control but also to rest of other treatments.